2011
DOI: 10.1002/adma.201101516
|View full text |Cite
|
Sign up to set email alerts
|

Nanofibrous Lipid Membranes Capable of Functionally Immobilizing Antibodies and Capturing Specific Cells

Abstract: Polymerizable cholesteryl‐succinyl silane was synthesized and fabricated into stable nanofibrous lipid membranes using a combined sol‐gel and electrospinning process. The resulting nanofibrous lipid membranes are capable of functionally immobilizing membrane proteins such as antibodies, thereby enabling targeted cell capture via the antigen‐antibody interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
34
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 34 publications
0
34
0
Order By: Relevance
“…However, the selection of protein-or peptide-based functionalities that can be incorporated onto synthetic polymer nanofibers may be limited by the harsh conditions of fiber spinning or by the particular conjugation chemistry that only works for certain biomolecules. Here, we envision that the coating of electrospun polycaprolactone (PCL) fibers with cholesteryl succinyl silane (CSS) and the subsequent CSS-mediated anti- [19]. Recently, we have demonstrated that the CSS fibers possess a greater ability to functionally immobilize antibodies for cell capture than the PCL and plasmatreated PCL fibers do [20].…”
Section: Introductionmentioning
confidence: 99%
“…However, the selection of protein-or peptide-based functionalities that can be incorporated onto synthetic polymer nanofibers may be limited by the harsh conditions of fiber spinning or by the particular conjugation chemistry that only works for certain biomolecules. Here, we envision that the coating of electrospun polycaprolactone (PCL) fibers with cholesteryl succinyl silane (CSS) and the subsequent CSS-mediated anti- [19]. Recently, we have demonstrated that the CSS fibers possess a greater ability to functionally immobilize antibodies for cell capture than the PCL and plasmatreated PCL fibers do [20].…”
Section: Introductionmentioning
confidence: 99%
“…The CSS nanofibers were formed via a combined sol-gel and electrospinning mechanism. 5 As illustrated in Fig. 1(b), the CSS nanofibers are composed of multiple layers of entangled cylindrical micelles.…”
mentioning
confidence: 99%
“…Previously, we reported that electrospun organic-inorganic lipid nanofibers are capable of functionally immobilizing Abs and capturing targeted cells without any chemical treatment. 5 In this study, we examine the underlying mechanism of Ab immobilization on the electrospun lipid nanofibers and illustrate the nanotopographic effects of the lipid nanofibers on cell capture.…”
mentioning
confidence: 99%
See 2 more Smart Citations